Degrees of Dignity - Buckner, Elizabeth (University of Toronto Press, 2023)
Presenting an analysis of higher education in eight countries in the Arab Middle East and North Africa, Degrees of Dignity works to dismantle narratives of crisis and assert approaches to institutional reform. Drawing on policy documents, media narratives, interviews, and personal experiences, Elizabeth Buckner explores how apolitical external reform models become contested and modified by local actors in ways that are simultaneously complicated, surprising, and even inspiring. Degrees of Dignity documents how the global discourses of neoliberalism have legitimized specific policy models for higher education reform in the Arab world, including quality assurance, privatization, and internationalization. Through a multi-level and comparative analysis, this book examines how policy models are implemented, with often complex results, in countries throughout the region. Ultimately, Degrees of Dignity calls on the field of higher education development to rethink current approaches to higher education reform: rather than viewing the Arab world as a site for intervention, it argues that the Arab world can act as a source for insight on resilient higher education systems.